Ethnographies and/of violence. (September 2019) - Jones, Gareth A.; Rodgers, Dennis
This paper examines ethnography as both a methodological practice and a form of writing, and specifically how ethnography as a textual product may shape and be shaped by the methodological process. We argue that a critical discussion of this relationship is especially important in relation to the ethnography/ethnographies of violence. Examining a range of recent texts, we consider whether different forms of violence necessitate, or have prompted, different styles of ethnographic writing. The paper raises questions about how decisions to adopt particular styles of writing can affect the substance of empirical material, and we reflect on the use of testimonio, biography and quasi-novel, as well as issues of anonymity and composite characterisation. Finally, the paper introduces the special issue contributions from five authors, who were invited to contribute reflections on the multiple ways in which their field method has intersected with representation, textually and intellectually.